Symbolic non-violence in the work of teachers in alternative education settings. Issue 1 (2nd January 2017) - Waters, Richard
Abstract: Patterns in analysis of research data on alternative education practices as well as on student and teacher experience in mainstream settings seem to support Pierre Bourdieu and Jean Claude Passeron's theory of symbolic violence. Data from teachers and students suggest that students from low socio-economic backgrounds often disengage from education because of their perceived failure as students. The research data also suggest that structures, practices and relationships in alternative education settings could be characterised as symbolic non-violence. This concept is explored in this paper with a view to clarifying critique of Bourdieu and Passeron as well as understanding the work of teachers in alternative settings and the role of non-violence in education. The article also considers what emergent ideas can be gained for the mainstream in suggesting new ways of supporting students from low socio-economic status backgrounds who are often marginalised in the education system. This could be achieved by changing the way school works rather than trying to change students to fit into existing school structures, practices and relationships.